Synthesis, antiplatelet and antithrombotic activities of resveratrol derivatives with NO-donor properties - Dutra, Luiz Antonio [UNESP] (2017)
Resveratrol (RVT) is a stilbene with a protective effect on the cardiovascular system; however, drawbacks including low bioavailability and fast metabolism limit its efficacy. In this work we described new resveratrol derivatives with nitric oxide (NO) release properties, ability to inhibit platelet aggregation and in vivo antithrombotic effect. Compounds (4a–f) were able to release NO in vitro, at levels ranging from 24.1% to 27.4%. All compounds (2a–f and 4a–f) have exhibited platelet aggregation inhibition using as agonists ADP, collagen and arachidonic acid. The most active compound (4f) showed reduced bleeding time compared to acetylsalicylic acid (ASA) and protected up to 80% against in vivo thromboembolic events. These findings suggest that hybrid resveratrol-furoxan (4f) is a novel lead compound able to prevent platelet aggregation and thromboembolic events.